Post-angiography spontaneous closure of cavernous sinus dural arteriovenous fistula: case report in Indonesia - Affan Permana; Stevanus Samudra; Fabianto Santoso; Adiguno Wicaksono (Egyptian Journal of Neurosurgery)
Abstract Intracranial cases of dural arteriovenous fistulas (dAVF) with spontaneous closure rarely occur. We reported a cavernous sinus dAVF (CS-DAVF) that closed spontaneously only after angiography. The patient complained of redness of left eye with reduced visual acuity, chemosis, retro-orbital pain, and ophthalmoplegia. The patient was compos mentis with anisocoria (right pupil with 3 mm diameter and left pupil with 5 mm diameter) and negative pupillary right reflex except the direct pupillary light reflex at the right eye. Diagnostic digital subtraction angiography (DSA) was performed two times without any intervention. The contrast could not fill the superior ophthalmic vein at the second DSA. At the therapeutic DSA a month later, the fistula between left and right meningohypophyseal trunk toward the cavernous sinus was no longer identified. We hypothesized that the phenomenon of spontaneous dAVF closure is similar by the mechanism according to publication by Al-Afif et al. as the patient had no history of trauma and only received diagnostic angiography procedure along with the contrast that used for the procedure.